Changes in chemical composition of cover crops residue during decomposition - Weiler,Douglas Adams (2022)
ABSTRACT: Crop residues decomposition are controlled by chemical tissue components. This study evaluated changes on plant tissue components, separated by the Van Soest partitioning method, during cover crop decomposition. The Van Soest soluble fraction was the first to be released from the crop residues, followed by cellulose and hemicellulose. Lignin was the crop residue component that suffered the least degradation, and for certain crop residue types, lignin degradation was not detected. The degradation of the main components of crop residues (soluble fraction, cellulose, hemicellulose and lignin) is determined by the chemical and structural composition of each fraction.